AI Application in Accounting Studies - Taqi, Muhamad (Review on Islamic Accounting, 2024)
This study aims to see the development of research on the topic of "Artificial Intelligence in Accounting" and research plans that can be carried out based on journals published on the theme. This research uses a qualitative method with a bibliometric analysis approach. The data used is secondary data with the theme "Artificial Intelligence in Accounting" which comes from the Scopus database with a total of 181 journal articles. Then, the data is processed and analyzed using the VosViewer application with the aim of knowing the bibliometric map of "Artificial Intelligence in Accounting" research development in the world. The results of the study found that there were 6 clusters with the most used words being impact, quality, adoption, challenge, firm, relationship, factor, value, and industry. Then, the research path topics related to Artificial Intelligence in Accounting are The impact of AI on auditing practice, AI and automation in accounting, AI adoption in accounting education, Blockchain adoption in accounting firms, Artificial intelligence in financial reporting, and AI integration in AIS.